Evaluation of volatile organic compounds in brown and red sub-Antarctic macroalgae - Berneira, Lucas Moraes; da Silva, Caroline Carapina; Passos, Luan Ferreira; Mansilla Muñoz, Andres Omar; dos Santos, Marco Aurelio Ziemann; de Pereira, Claudio Martin Pereira (My University, 2021)
Volatile organic compounds (VOCs) comprise a wide range of compounds with low molecular weight that are released from seaweeds as secondary metabolites. Therefore, the aim of this work was to evaluate the profile of VOCs from six sub-Antarctic macroalgae by means of gas chromatography-mass spectrometry. Results indicated that the studied seaweeds contained approximately 40 different compounds found as aldehydes, ketones, hydrocarbons and alcohols, for instance. For brown macroalgae, hexanal was found in greater amounts (12.87-29.46%) followed by 2-pentylfuran (5.52-11.61%) and pentadecane (4.29-10.28%), while red seaweeds were mainly composed of heptadecane (27.79-85.12%), hexanal (1.78-11.62%) and benzaldehyde (1.36-2.87%). Further evaluation using principal component analysis showed that distinct compositions of VOCs could differentiate brown and red seaweeds. Therefore, sub-Antarctic macroalgae had their VOCs elucidated for the first time assisting in the efforts for understanding their biochemical constitution as well as supporting in further potential pharmacological and biotechnological applications.
Keywords: gas chromatography-mass spectrometry; ochrophyta; rhodophyta; sub-antarctic region; volatile organic compounds